A concentrate-and-destroy technique for degradation of perfluorooctanoic acid in water using a new adsorptive photocatalyst. (15th October 2020) - Li, Fan; Wei, Zongsu; He, Ke; Blaney, Lee; Cheng, Xinquan; Xu, Tianyuan; Liu, Wen; Zhao, Dongye
Highlights: Prepared a sorptive photocatalyst (Fe/TNTs@AC) based on activated carbon and TiO2 . Fe/TNTs@AC exhibited synergistic adsorption and photocatalytic activity. Fe/TNTs@AC was able to rapidly adsorb and concentrate PFOA on the photoactive sites. Fe/TNTs@AC degraded >90% of sorbed PFOA in 4 h under UV and mineralized 62%. The photodegradation also regenerates Fe/TNTs@AC, allowing for material reuses. Abstract: Per- and polyfluoroalkyl substances (PFAS) have emerged as a major concern in aquatic systems worldwide due to their widespread applications and health concerns. Perfluorooctanoic acid (PFOA) is one of the most-detected PFAS. Yet, a cost-effective technology has been lacking for the degradation of PFAS due to their resistance to conventional treatment processes. To address this challenge, we prepared a novel adsorptive photocatalyst, referred to Fe/TNTs@AC, based on low-cost commercial activated carbon (AC) and TiO2 . The composite material exhibited synergistic adsorption and photocatalytic activity and enabled a novel "concentrate-&-destroy" strategy for rapid and complete degradation of PFOA in water. Fe/TNTs@AC was able to adsorb PFOA within a few minutes, thereby effectively concentrating the target contaminant on the photoactive sites. Subsequently, Fe/TNTs@AC was able to degrade >90% of PFOA that was preconcentrated on the solid in 4 h under UV irradiation (254 nm, 21 mW cm ‒2 ), of which 62% was completely mineralized to F − . The efficient photodegradation also regenerated Fe/TNTs@AC, eliminating the need for expensive chemical regenerants, and after six cycles of adsorption/photodegradation, the material showed no significant drop in adsorption capacity or photocatalytic activity. Simulations based on the density functional theory (DFT) revealed that Fe/TNTs@AC adsorbs PFOA in the side-on parallel mode, facilitating the subsequent photocatalytic degradation of PFOA. According to the DFT analysis, scavenger tests, and analysis of degradation intermediates, PFOA decomposition is initiated by direct hole oxidation, which activates the molecule and leads to a series of decarboxylation, C–F bond cleavage, and chain shortening reactions. The innovative "concentrate-&-destroy" strategy may significantly advance conventional adsorption or photochemical treatment of PFAS-contaminated water and holds the potential to degrade PFOA, and potentially other PFAS, more cost-effectively. Graphical abstract: Image, graphical abstract